Alcoholic liver disease: pathogenesis and new targets for therapy - Altamirano, José; Bataller, Ramón (Nature reviews. Gastroenterology & hepatology, 2011)
Despite its high prevalence worldwide, alcoholic liver disease (ALD) has attracted little attention in the past two decades. Abstinence has been the most effective therapy, but targeted therapies are required for severe forms. Novel potential therapeutic targets have been identified, but their pathogenetic roles remain unknown. This Review summarizes the epidemiology, risk factors and current knowledge of ALD, including discussion of new therapeutic targets. Alcoholic liver disease (ALD) is a major cause of morbidity and mortality worldwide. The spectrum of disease ranges from fatty liver to hepatic inflammation, necrosis, progressive fibrosis and hepatocellular carcinoma. In developed countries, ALD is a major cause of end-stage liver disease that requires transplantation. The most effective therapy for ALD is alcohol abstinence. However, for patients with severe forms of ALD (that is, alcoholic hepatitis) and for those who do not achieve abstinence from alcohol, targeted therapies are urgently needed. The development of new drugs for ALD is hampered by the scarcity of studies and the drawbacks of existing animal models, which do not reflect all the features of the human disease. However, translational research using liver samples from patients with ALD has identified new potential therapeutic targets, such as CXC chemokines, osteopontin and tumor necrosis factor receptor superfamily member 12A. The pathogenetic roles of these targets, however, remain to be confirmed in animal models. This Review summarizes the epidemiology, natural history, risk factors and current knowledge of the pathogenetic mechanisms of ALD. In addition, this article provides a detailed description of the findings of these translational studies and of the animal models used to study ALD. Key Points Alcohol abuse is a major cause of preventable morbidity and mortality worldwide, and a major health problem in both the EU and the USA Alcoholic liver disease is a major cause of end-stage liver disease requiring liver transplantation The spectrum of alcoholic liver disease encompasses simple steatosis, steatohepatitis, progressive fibrosis, cirrhosis and hepatocellular carcinoma The basic mechanisms of alcoholic liver disease have been evaluated in both animal models and translational studies, but further research is needed to confirm the results Studies in human liver samples have identified novel therapeutic targets for alcoholic liver disease, including CXC chemokines, osteopontin, tumor necrosis factor receptor superfamily member 12A receptor and nostrin New experimental models of severe alcoholic liver disease that include profound hepatocellular damage and fibrosis should be developed